‘Neopredeljonnyj’ [Indefinite] vs. ‘Neulovimyj’ [Elusive] in Aspect of Categorical Perception - L. V. Kalinina (Научный диалог)
The article discusses the phenomenon of categorical perception, the success of which the author suggests can be expressed by the formula “this is exactly X from the category ‘X’.” The lexemes ‘neopredeljonnyj’ [indefinite] vs. ‘neulovimyj’ [elusive] are considered as units that verbalize the subject’s categorization difficulties in perception. Based on a comparison of the use of the adjectives ‘neopredeljonnyj’ [indefinite] vs. ‘neulovimyj’ [elusive] with nominations of different types of perceptual perception, it is established in which cases the object of perception, causing categorization difficulties, is designated as ‘neopredeljonnyj’ [indefinite] X and in which cases it is designated as ‘neulovimyj’ [elusive] X. The study is carried out using methods of definitional, componential, distributive, and contextual analysis based on explanatory dictionaries and data from the Russian National Corpus. As a result of the analysis of linguistic material, it was revealed that the combination ‘neopredeljonnyj’ [indefinite] X denotes that a certain X is well perceived by the sense organs, but the subject is unaware (it is absent from their lexicon) of the designation for this X. The combination ‘neulovimyj’ [elusive] X denotes that the sense organs only register the presence of a certain X, while X manifests itself too quickly/weakly or is heterogeneous, making it unrecognizable.